Evaluación de la obtención de diésel a nivel laboratorio mediante pirólisis a partir de residuos plásticos provenientes del proceso de empacado en la empresa Atlantic FS S.A.S. (2018)
Initially transparent plastic waste from the company Atlantic FS S.A.S. are taken to a pre-treatment process that consists of washing, drying and decreasing the size of the material. Then the raw material is characterized by physicochemical methods, identifying that it is composed of polyethylene, polypropylene and polyamide. The operating conditions for each chemical recycling process are set at 280 minutes of residence time and 1 kg of raw material. In the same way, the temperature levels to be evaluated are set at 600 and 650° C, while for the concentration of catalyst, levels of 5, 10 and 15% w/w are chosen. The data of the 2x3 experiment design are studied by a statistical analysis of variance ANOVA, with which it is affirmed that both the temperature and catalyst concentration factors, as well as the interaction between them, have an effect in the conversion of the material to pyrolytic oil. The highest oil yield value obtained experimentally was 74% with a temperature of 650 ° C and a catalyst concentration of 5% w/w. To predict the performance of this hydrocarbon according to the operating conditions, the data is adjusted to a linear regression model. In order to know the hydrocarbons present in the oils, atmospheric distillations are carried out, through which it is observed that diesel, kerosene and some heavy compounds are present in this liquid pyrolytic phase. The highest proportion of diesel was 51% and was obtained in the oil produced at 600 ° C and 15% w/w. Additionally, tests are done to characterize the diesel, finding that it is of good quality since it complies with current regulations for the current diesel. Finally, the overall performance of the process is calculated, where 31% is found for the diesel obtained with chemical recycling at 650 ° C and 5% w/w of catalyst.